Refleksivnost diskurza pri mednarodnih govorcih - Mauranen, Anna (Jezik in slovstvo, 2007)
English has become the global language of science and scholarship, used overwhelmingly by non-native speakers. This makes English as a lingua franca (ELF) an intriguing area of research into variation and change: when one language is in contact with virtually any other language in the world, what happens to this language? Discourse features are a case in point: we may assume that discourse reflexivity increases in lingua franca use. It makes discourse more explicit, which is important in multicultural encounters. This paper explores discourse reflexivity in the speech of people using English as a lingua franca in university settings. Findings suggest that reflexive functions and discourse collocations operate in ELF in a similar way to L1 English. Differences appear at a more subtle level of form-function relationships: in ELF speech, forms were often approximate rather than accurate, some form-function pairings were ignored, and some specific, minor functions of certain expressions were not used.
Keywords: Corpus linguistics; korpusno jezikoslovje; uporabno jezikoslovje; lingua franca; jeziki v stiku; angleščina; English